2018
DOI: 10.1038/nature26140
|View full text |Cite
|
Sign up to set email alerts
|

The protein histidine phosphatase LHPP is a tumour suppressor

Abstract: Histidine phosphorylation, the so-called hidden phosphoproteome, is a poorly characterized post-translational modification of proteins. Here we describe a role of histidine phosphorylation in tumorigenesis. Proteomic analysis of 12 tumours from an mTOR-driven hepatocellular carcinoma mouse model revealed that NME1 and NME2, the only known mammalian histidine kinases, were upregulated. Conversely, expression of the putative histidine phosphatase LHPP was downregulated specifically in the tumours. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
196
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 175 publications
(208 citation statements)
references
References 41 publications
6
196
2
Order By: Relevance
“…In our study, the results here indicated that LHPP was markedly reduced in AFP‐NHCC cancer tissues, consistent with previous studies by Hindupur et al Targetscan, miRanda, miRDB, and TangetMiner software combined with luciferase reporter detection indicated that miR‐363‐5p and miR‐765 were involved in the targeted regulation of LHPP. Further, the current study screened miR‐363‐5p and miR‐765 to downregulate the expression of LHPP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the results here indicated that LHPP was markedly reduced in AFP‐NHCC cancer tissues, consistent with previous studies by Hindupur et al Targetscan, miRanda, miRDB, and TangetMiner software combined with luciferase reporter detection indicated that miR‐363‐5p and miR‐765 were involved in the targeted regulation of LHPP. Further, the current study screened miR‐363‐5p and miR‐765 to downregulate the expression of LHPP.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, identification of an effective diagnostic model for HCC is of great importance for patients, particularly for AFP‐NHCC patients. Recently, LHPP is reported to play an essential role in inhibiting human HCC progression by regulating phosphatidylinositol‐3‐kinase/protein kinase B (PI3K/AKT) signaling pathway, and the loss of LHPP expression is also associated with reduced survival in HCC . Zheng et al also found that LHPP expression levels were markedly reduced in human cervical cancer tissue samples compared to the adjacent normal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Hindupur and co‐workers demonstrated that LHPP was a protein pHis hydrolase, with potential physiological substrates, including ACLY, histone H2A.V, and RNA polymeraseassociated protein LEO1 . These substrates were identified through immunoprecipitation with pHis‐specific antibodies from lysates of CB1 cells lacking LHPP.…”
Section: Chemistry Of Protein N‐phosphoramidatesmentioning
confidence: 98%
“…Although these early reports of pLys hydrolase activities did not reveal the identity of the responsible enzymes, more recent studies found that PHPT1, which is best known as a protein pHis hydrolase, also dephosphorylated poly(pLys) and chemically Lys‐phosphorylated histone H1 . LHPP, another mammalian pHis phosphatase (see Section 3.2), also hydrolyzed pLys monomer, but it is unknown whether it is active towards pLys in protein substrates.…”
Section: Phospholysine Hydrolasesmentioning
confidence: 99%